Coordinated neuron-glia regeneration through Notch signaling in planarians. - M Lucila Scimone; Bryanna Isela-Inez Canales; Patrick Aoude; Kutay D Atabay; Peter W Reddien (PLoS Genetics)
Some animals can regenerate large missing regions of their nervous system, requiring mechanisms to restore the pattern, numbers, and wiring of diverse neuron classes. Because injuries are unpredictable, regeneration must be accomplished from an unlimited number of starting points. Coordinated regeneration of neuron-glia architecture is thus a major challenge and remains poorly understood. In planarians, neurons and glia are regenerated from distinct progenitors. We found that planarians first regenerate neurons expressing a Delta-encoding gene, delta-2, at key positions in the central and peripheral nervous systems. Planarian glia are specified later from dispersed Notch-1-expressing mesoderm-like phagocytic progenitors. Inhibition of delta-2 or notch-1 severely reduced glia in planarians, but did not affect the specification of other phagocytic cell types. Loss of several delta-2-expressing neuron classes prevented differentiation of the glia associated with them, whereas transplantation of delta-2-expressing photoreceptor neurons was sufficient for glia formation at an ectopic location. Our results suggest a model in which patterned delta-2-expressing neurons instruct phagocytic progenitors to locally differentiate into glia, presenting a mechanism for coordinated regeneration of numbers and pattern of cell types.